대순진리회의 시간관 연구 (II) - 재조정되고 통치되는 시간을 중심으로 - 차선근; Cha Seon-keun (大巡思想論叢, 2024)
One notable characteristic of Daesoon Jinrihoe's view of time, is its perception of time as a passive entity. This signifies that, in the context of Daesoon Jinrihoe, time is subject to influence through experience, specifically undergoing re-calibration or governance. The summary of this perspective is as follows: Firstly, Daesoon Jinrihoe's understanding of time incorporates a historical viewpoint characterized by the law of entropy, which posits that disorder increases as time progresses. Secondly, within the world established by Daesoon Jinrihoe, time experiences transformation before and after the Great Opening. Prior to this event, time follows a helical model characterized by increasing chaotic disorder, whereas in the Later World, the helical model reflects only Mutual Beneficence, symbolizing progress and development in the era. Thirdly, the Great Opening re-calibrates time, serving as the criterion for determining human life. Prior to the Great Opening, time recorded human life in a manner marked by Mutual Contention, whereas afterward, it will record human life as being characterized by Mutual Beneficence. This re-calibration of time leads precisely to directional (spatial) re-calibration. Fourthly, the Great Opening re-calibrates the order of time and space. In the Former World, space held precedence over time. However, the Great Opening changes this dynamic, with time assuming precedence over space in the Later World. In this context, the integration of time and space establishes a worldview. Fifthly, in the worldview of Daesoon Jinrihoe, time serves as a vehicle for the governance of the Supreme God. The Supreme God governs all things by controlling time, orchestrating changes spanning birth (saeng, 生), growth (jang, 長), harvest (yeom, 斂), and storage (jang, 藏), much like how problems are resolved through natural progress without requiring deliberate action. Lastly, time functions as a medium through which entities that strive to achieve unification with the Dao come to govern all things. For this reason, achieving unification with the Dao in Daesoon Jinrihoe specifically refers to the governance of time. 대순진리회 시간관의 특징 가운데 하나는 시간을 수동형으로 본다는 사실이다. 이 말은 시간이 경험자로부터 영향을 받는다는 뜻이다. 즉, 대순진리회에서 시간은 재조정되기도 하고 다스려지기도 한다. 그 내용을 요약하자면 다음과 같다: 첫째, 대순진리회 시간관은 시간의 흐름과 함께 무질서가 증가한다는 엔트로피 법칙의 역사관을 포함한다. 둘째, 대순진리회가 구축하는 세계에서 시간은 개벽 전후로 그 성격이 바뀐다. 개벽 이전은 상극시대의 무질서 증가 나선형 시간, 후천은 상생만 존재하는 시대의 진보와 발전 나선형 시간이다. 셋째, 개벽은 시간을 재조정한다. 시간은 인간 삶을 결정하는 표준으로 기능하는데, 개벽 이전의 시간은 인간 삶을 상극으로, 개벽 이후의 시간은 인간 삶을 상생으로 기록하기 때문이다. 시간의 재조정은 곧 방위(공간)의 재조정으로 이어진다. 넷째, 개벽은 시간과 공간의 순서를 재조정한다. 선천에는 공간이 시간을 앞섰고, 개벽은 그것을 뒤집어 후천에 시간이 공간을 앞서도록 만든다. 이로써 시공간 통합의 세계관이 구축된다. 다섯째, 대순진리회 세계에서 시간은 최고신이 다스림을 펴기 위해 사용하는 도구다. 최고신은 생장염장(生長斂藏)의 변화를 일으키는 시간 통치로써 만물을 무위이화로 다스린다. 여섯째, 시간은 후천에 도통이라는 목표에 도달한 존재들이 만물을 통치하는 데 활용하는 도구로 기능한다. 이 때문에 대순진리회의 도통은 곧 시간을 다스림을 의미한다.